Hizb al-Tahrir: Founding and determinants of cultural and political Â©discourse - Heraz, Wael; Abdul Hamid, Faisal Ahmad Faisal (Journal Al-Muqaddimah, 2017)
Hizb UT-Tahrir, which was founded in 1953, is considered one of the most controversial Islamic political parties in terms of its cultural and political ideas. Although more than 60 years have passed since the founding of the party, the academic studies on the party are still few compared to other Islamic parties. This study aims at filling a gap in terms of the history of the party's march, based on primary sources close to the founders and then clarifying the most important cultural and political ideas of the party, depending on the primary sources published by the party during his career. This study tries to put the reader close to the party from the historical point of view, which contributed to the emergence of the party and then the basis of the methodological culture adopted by the party and finally the political foundations under which the party works to develop political analysis issued by its members and then to society.